Limb-Girdle Muscular Dystrophies (LGMD): Clinical features, diagnosis and genetic variability through next generation sequencing - Priyanshu Mathur; Ashmeet Kaur; Urvashi Vijay; Ashok Gupta; Kamlesh Agarwal; Lokesh Agrawal (Global Medical Genetics)
Background: Limb-Girdle Muscular Dystrophy (LGMD) is a rare heterogeneous group of neuromuscular disorders distinguished by progressive weakness of limb-girdle muscles. Diagnosis of LGMD is a challenging task and requires multiple obligatory assays. Objective: To study the epidemiology, clinical features, the genetic variability in patients diagnosed with LGMD through Next Generation Sequencing. Material and Method: A retrospective study of 27 patients suspected of LGMD was done to study the phenotypic presentation and the genotypic alteration of the patients, presenting to a tertiary care center in Rajasthan were studied. Results: Out of the twenty-seven patients suspected of LGMD, nineteen patients took genetic tests, while eight patients underwent biopsy. Among the nineteen patients, seventeen patients were identified with pathogenic mutations. Autosomal Recessive (LGMD-R) was the most common subgroup in this cohort. In the LGMD R1 subgroup, the most common mutation was c.2051–1 G>T and the exon hotspot was 18–22. The deleterious mutations in the LGMD R2 subgroup were distributed along the entire coding sequence, without any hotspot. However, C2E, C2F, and DysF domains contain variants at higher frequencies. The types of mutations were mostly point mutations (34 % of missense mutations and 66 % of nonsense mutations). We identified one novel mutation which was considered as a stop codon. Patients(n = 8) who underwent muscle biopsy for immunohistochemistry, had absent/reduced sarcoglycan uptake (n = 4) or absent dysferlin (n = 2) on the sarcolemma, while the remaining two biopsies were inconclusive (due to multiple protein deficiencies).